Impact of Outsourcing on service providers: evidence from the textile industry of Pakistan - Naqvi, Muhammad Moied Abbas Naqvi (2021)
Most of the focus has been on the client’s side. The internet and articles are mostly occupied of what outsourcing means for outsourcer and what are the pros and cons from their perspective. This research paper on the other hand is focusing on the Pakistani textile outsourcing service provider/supplier. The perspectives of the supplier will be the focal point of this research paper. What do they think about the idea of outsourcing and are they willing to promote or demote it? The thematic analytical approach is carried out. The complete data was organized and classified into codes under a particular named category from a total of 6 named categories listed. And the scattered coding was narrowed down to a total of 5 themes which are Businesses being outsourced, Vendor’s performance in outsourcing, Vendor’s risks in outsourcing, Vendor’s motivation towards outsourcing and Scope of being outsourced. The results show that there are some issues that service providers think outsourcing brings but all three business’s perspective in the end was very much similar being in the favour of outsourcing where they fully backed it up by their extensive future strategies. Based on these conclusions business should raise their international activity by both increasing the number of clients they work for as well as the quality of work they do for each one of them. On the other hand, government as well as other financial institutions should also play their part in supporting the textile vendors to become one of the top service providers in the world.